Written asthma action plan in emergency department improves knowledge and asthma control among adult acute asthma patients - Shamsuriani Md Jamal,; Norhidayah MS, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Self-management of asthma using the written asthma action plan (WAAP) is important in ensuring effective management of asthma as it reduces hospital visits. This study evaluates the improvement in knowledge and asthma control using WAAP among adult patients with acute asthma presenting to Emergency Department (ED). This randomized control trial was conducted over a 19-month period in an ED of a university hospital. Adult patients with acute mild to moderate asthma were included in the study. Patients were randomized into intervention and control group. A self-administered knowledge questionnaire was distributed to all patients. Both groups received asthma counselling guided by asthma flyers. The intervention group was further counselled on individualized WAAP. The control group received standard verbal advice upon discharge. Subsequently at 1 month and 3 months a follow up was conducted. Knowledge and asthma control were assessed via a telephone survey. Fifty patients were assigned randomly to intervention (WAAP) and control group. Each group received 25 patients. The knowledge score of the intervention group was significantly more than the control group (16.88+0.44 vs 13.36+3.72; p<0.001). The intervention group achieved good asthma control (ACT score >19) at 1 month compared to control group (20.64+3.26 vs 17.72+4.17). Both groups achieved good control at 3 months follow up. Self-management with WAAP in ED improves knowledge and asthma control among acute mild to moderate asthma patients.